Nivel de seguridad de atención de pacientes en los servicios de emergencia en la red hospitalaria - Juarez Morillo, Rocio Edith (2019)
This quantitative-descriptive and cross-sectional research, applied to a single population, was aimed to determine the level of safety of patients’ care in the Emergency Services in the hospitals II – 1 of Trujillo Province. The population consisted of the seven district hospitals of the Trujillo Health Services Network at level II – 1. The sample was censal because the total number of hospitals consisting of La Noria, Santa Isabel, El Esfuerzo, Walter Cruz Vilca, Jerusalem, Laredo and Vista Alegre were studied. When processing information to determine the level of safety of patients’ care in the Emergency Services, it was found according to the final weight and condition of each health center, that 57% of hospitals promote good care and safety practices in the emergency services, while 43% of hospitals do not promote such practices in the second hospital level of the Trujillo Network.